AWARENESS OF INTERDISCIPLINARY ORTHODONTIC-ENDODONTIC PATIENT MANAGEMENT AMONG THE DENTAL PRACTITIONERS OF HAZARA DIVISION - Wasim Ijaz; Asim Qureshi; Naveed Khan; Naveed Iqbal; Abid Hussain; Eizza Niaz (Pakistan Oral & Dental Journal, 2024)
Background: Collaborative orthodontic-endodontic approaches are vital in addressing complex dental cases. However, existing literature reveals a notable dearth in understanding and implementing this approach among dental practitioners. Objective: This study aimed to bridge the gap in understanding current practices among dental practitioners, fostering enhanced patient care and ethical standards. This cross-sectional survey, conducted from September 1st to 30th, 2023, involved distributing a validated questionnaire to dental practitioners in the Hazara Division, yielding 96 responses from 105 visited clinics and 44 from hospitals. Descriptive statistics were used for frequencies and percentages using SPSS version 23. Methodology: The survey involved 78.6% general dentists, 13.6% orthodontists, and 7.9% endodontists. Varying levels of correct responses were observed for the knowledge-based questions. Results: Positive attitudes were seen, with 70% of respondents expressing an interest in enhancing knowledge through educational programs, and 73% agreeing to adhere to interdisciplinary guidelines. Furthermore, 79.3% of practitioners had experience treating cases requiring both orthodontic tooth movement and endodontic therapy. Conclusion: Notably, orthodontists and endodontists showed higher percentages of accurate responses compared to general dentists. In conclusion, this study underscores the need for improved education, standardized protocols, and better patient communication for effective interdisciplinary dental care specifically in general dental practitioners.